Tumor tissue Helicobacter pylori and human papillomavirus infection in head and neck squamous cell carcinoma patients and association with clinicopathological indices: A cross-sectional medical survey - Nooshin Mohtasham; Nasrollah Saghravanian; Reza Zare; Shadi Saghafi; Narges Ghazi; Farnaz Mohajertehran; Mehdi Shahabinejad (Wolters Kluwer Medknow Publications, 2022)
Background: The associations between Helicobacter pylori and human papillomavirus (HPV) with head and neck squamous cell carcinomas (HNSCCs) are approved before. However, the association between demographic, clinicopathological, and histologic characteristics of HNSCC patients and molecular detection of HPV and H. pylori has not been enough investigated. Materials and Methods: In this cross-sectional study, 62 patients with HNSCC from January 2016 to February 2020 were entered the study. For H. pylori detection 16S ribosomal RNA and glmM genes and HPV detection, MY09 and MY11 genes were used. P < 0.05 is considered as significant level. Results: There were 34 patients with advanced-stage cancer (54.8%). Grade I patients (61.3%) had the highest frequency. There were 20 (32.25%) and 7 (11.29%) patients with positive H. pylori infection among tumor tissue and healthy tissue margins, respectively. Positive HPV infections were in 8 (12.90%) and 3 (4.83%) patients, respectively, in tumor tissue and healthy tissue margins (P = 0.01). There was a significant difference between histological grade and infection to HPV among HNSCC patients (P = 0.01), and most of the positive HPV cases had well-, moderate-, and poorly-differentiated tumors, respectively. Our study showed a significant increase in HPV infection in the advanced-stage group compared to the early-stage group (P = 0.05). Conclusion: Our study findings concluded a significant relationship between HPV infection in HNSCC patients with age, stage, and grade. In summary, our findings based on polymerase chain reaction analysis concluded remarkably a potential role of HPV infection and to some extent H. pylori infection into the contribution of HNSCC malignancies.